An Assessment of the Dynamic of Religious Ritualism in Sporting Environments - Fernández, Oscar (Journal of religion and health, 2014)
The main focus of this study is the analysis of the link between sport, leisure and the behavior, and phenomenon of religion. From the qualitative point of view of social anthropology, fieldwork has been carried out with different informers from different sporting environments. Rather than directly show the fieldwork itself, we have decided to present an interpretation of it through an analysis of the environments, behaviors, attitudes, the discourse of leisure and sport and its relationship with market forces, advertising and the media. In this regard, we point out a reality which for some people is their conscience or reason for being, opening new directions of study and viewpoints in this area of sporting and health studies.